Industrial strategies and solutions for 3D printing : applications and optimization - Vanaei, Hamid Reza; Khelladi, Sofiane; Tcharkhtchi, Abbas; Ohio Library and Information Network (Hoboken, New Jersey : John Wiley & Sons, Inc., 2024)
Industrial Strategies and Solutions for 3D Printing: Applications and Optimization offers a comprehensive overview of the 3D printing process, covering relevant materials, control factors, cutting-edge concepts, and applications across various industries such as architecture, engineering, medical, jewelry, footwear, and industrial design. While many published books and review papers have explored various aspects of 3D printing, they often approach the topic from a specific perspective. This book instead views 3D printing as a multidisciplinary field, extending beyond its rapid growth into emerging areas like data science and artificial intelligence
Keywords: Three-dimensional printing -- Industrial applications